ANALISIS SISTEM PENILAIAN PEMBELAJARAN SEJARAH BERDASARKAN KURIKULUM 2013 DI SMA NEGERI 2 SUKOHARJO - Aji, Mpu Tabah Chalifatah; S, Leo Agung; Pelu, Musa (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2017)
The purposes of this study were to determine (1) learning assessment planning conducted by history teacher based on curriculum 2013 in SMA Negeri 2 Sukoharjo; (2) learning assessment implementation conducted by history teacher based on curriculum 2013 in SMA Negeri 2 Sukoharjo; (3) the obstacles faced by history teacher in learning assessment based on curriculum 2013 in SMA Negeri 2 Sukoharjo; (4) the solutions to overcome the obstacles experienced by history teacher in doing learning assessment based on curriculum 2013 in SMA Negeri 2 Sukoharjo.This study used descriptive qualitative method. Data were collected through observation, interview, and document analysis. Data validity was done through method triangulation and source triangulation. Technique of analyzing data used by the author was an interactive model of analysis.The results showed that (1) history learning assessment planning in SMA N 2 Sukoharjo has already matched with the reference in curriculum 2013, namely Education and Culture Minister Regulation Number 53 of 2015. The history teacher has made the design or implementation for knowledge (cognitive) aspect and skills (psychomotor) in the beginning of the semester. Besides, for attitude (affective) aspect, the teacher only uses instruments prepared by the school; (2) the implementation of history learning assessment based on curriculum 2013 in SMA N 2 Sukoharjo generally has been in accordance with the reference of assessment in curriculum 2013, namely Education and Culture Minister Regulation Number 53 of 2015. Learning assessment implementation on the aspects of attitude, knowledge, and skill showed that history teacher has already understood about various methods and assessments in curriculum 2013 impelementation; (3) the obstacles in the learning assessment of history subject based on curriculum 2013 in SMA Negeri 2 Sukoharjo, are: teacher difficulties in assessing students? attitude, the teacher doesn?t have enough time for students assessment based on curriculum 2013, too many students in one classroom make teacher difficult to assess students deeply, especially for attitude aspect; (4) The solutions in overcoming those obstacles, are: reproducing students? attitude assessment, starts from small things; Doing checking students? attendance in the beginning of the lesson; not assessing all indicators in one day, the important thing, in the end of the semester all indicators have been assessed; the school provides a simple application to facilitate teachers in calculating the final grade.